Intangible Heritage: An Analysis of Jordanian Customs Signifying Societal Interdependence and Social Solidarity - Karimah Suleiman Aljedayah; Suzie Yaseen Rababa'h; Osamah Fakeer Alrababah; Baker Mohammad Bani-Khair; Mahmoud Ali Ibrahim Rababah; Khaled Ahmed Faleh Al-Shloul; Muayyad Ghaleb Bany Hani (Journal of Islamic Thought and Civilization, 2024)
This study discusses a set of Jordanian customs and habits that characterize the Jordanian Arabic society. These custom and habits have played a key role in establishing interdependence and solidarity among Jordanian people in the past before the advent of modernity and civility. These include dakhalah, tu'mah, al'oneh, and inzalah. However, due to societal changes and the transition towards modernity, some of these customs have diminished and gradually disappeared from many parts of Jordan. To gather comprehensive data, interviews were conducted with 48 individuals who experienced and practiced these customs in different time periods. The results revealed that older participants still adhere to these authentic customs, contributing to increased intimacy and helping to navigate life's challenges. Some young and middle-aged participants recognized the significant impact of these customs on fostering love and intimacy, but chose to discontinue their practice when it conflicted with their time and financial constraints. On the other hand, some young participants perceived these customs as outdated and hindering their activities and progress. It is essential to signify these traditions importance and encourage their ongoing practice to protect Jordan's cultural heritage and retain the positive effects of these practices. By appreciating the importance of good habits in Jordanian culture, people may use them as a springboard to foster camaraderie, collaboration, and a sense of shared responsibility for the sake of a better future.